Membrane-type 6 matrix metalloproteinase (MT6-MMP, MMP-25) is the second glycosyl-phosphatidyl inositol (GPI)-anchored MMP. - Kojima, S; Itoh, Y; Matsumoto, S; Masuho, Y; Seiki, M (2000)
A recently identified membrane-type 6 matrix metalloproteinase (MT6-MMP) has a hydrophobic stretch of 24 amino acids at the C-terminus. This hydrophobicity pattern is similar to glycosyl-phosphatidyl inositol (GPI)-anchored MMP, MT4-MMP, and other GPI-anchored proteins. Thus, we tested the possibility that MT6-MMP was also a GPI-anchored proteinase. Our results showed that MT6-MMP as well as MT4-MMP were labeled with [3H]ethanolamine indicating the presence of a GPI unit with incorporated label. In addition, phosphatidyl inositol-specific phospholipase C treatment released MT6-MMP from the surface of transfected cells. These results strongly indicate that MT6-MMP is a GPI-anchored protein. Since two members of MT-MMPs are now assigned as GPI-anchored proteinase, MT-MMPs can be subgrouped into GPI type and transmembrane type.